MANAGEMENT OF SUSTAINABLE ECONOMIC DEVELOPMENT OF HOTEL AND RESTAURANT ENTERPRISES ON THE BASE OF ANALYSIS OF CURRENT COSTS - Yudina, O. I.; Stebliuk, N. F.; Mayko, O. V.; Zenina, D. O. (Systems and Technologies, 2023)
The article describes approaches to analyzing current production costs and assessing their quantitative impact of operating activities on the efficiency of hotel and restaurant enterprises, which are the basis for planning and managing the resource potentials and sustainable economic development of business entities. The main aim of this article is to establish the trends of quantitative relationship between the indicators of resource intensity and production efficiency and to determine the influence of current costs on the outcomes in order to ensure the possibility of managing these processes and sustainable economic development of enterprises. The models of production efficiency, using the means of economic-mathematical modeling, are built in this study. On the basis of the obtained mathematical equations, the trends of the quantitative relationship between production factors are explained, the estimated coefficients for the development of reserves of resource potentials of enterprises in the hotel and restaurant sphere are determined. Using the calculated estimation coefficients, the strength of the indirect and direct impact of a particular type of current costs on the efficiency of the operating activities of an economic entity, the share of contribution of a certain factor parameter into the total impact of all factors, the opportunities of income increasing through the development of resource potentials are determined. By interpreting the coefficients obtained as a result of the analysis, a mathematical formula for calculating reserves for the economic development of restaurant business establishments has been proposed, it allows to determine the level of profit growth due to changes in the amount of a certain resource (type of current costs), taking into account the share of its contribution to the integrated action of factors. The developed models and coefficients are the basis for managing the sustainable economic development of enterprises in the hotel and restaurant sector by planning the results of operating activities, percentage changes in performance indicators and economic growth of business entities. Thus, on the basis of the economic and mathematical models of efficiency of production activities of hotel and restaurant enterprises the coefficients of economic growth and reserve development are calculated. The differentiated and integrated impact of current costs on the overall result is determined, and approaches to determining the directions of economic growth and management of sustainable development of enterprises are proposed.